Odpowiedzi

2010-03-08T16:03:52+01:00
A) dla x= 0,4 i y=1,2
7 + (–3)(x – 2y) - 1/2(–4y + x) = 7 - 3x + 6y + 2y - 1/2x = 7- 3½x + 8y = 7 - 3½ × 0,4 + 8 × 1,2 = 7 - 1,4 + 9,6 = 15,2
b) dla x=0,6
4(x – 1) + 5(2x + 3) – 6(2 – x) = 4x - 4 + 10x + 15 - 12 + 6x = 20x - 1 = 20 × 0,6 - 1 = 12 - 1 = 11
5 2 5
2010-03-08T16:06:22+01:00
A)
7 + (–3)(x – 2y) - 1/2(–4y + x) dla x= 0,4 i y=1,2
7+(-3x+6y)+(2y-1/2x) = 7+(-3*0.4+6*1.2)+(2*1.2-1/2*0.4)
7+(-1.2+7.2)+2.4-0.2 = 7+6+2.2 = 15.2

b)
4(x – 1) + 5(2x + 3) – 6(2 – x) dla x=0,6
4x-4+10x+15-12+6x = 2,4-4+6+15-12+3.6 = 11
2 3 2